Effect of two-dimensional functional fillers size on the performance of BN/EPDM flexible neutron protection composite materials - ZONG Bo; ZENG Deyang; WANG Kaikai; TANG Wencai; FU Jiajia; CHANG Shuquan; HE Jialin; CHEN Fanglei; LI Ziping; LI Da (He jishu)
BackgroundFlexible neutron protection composite materials are of great significance for the protection of special-shaped components and personnel. Their performances are closely related to the properties of functional fillers, but the effect of size of 2D functional fillers on the performance of composites is not yet clear.PurposeThis study aims to explore the influence of two-dimensional (2D) functional filler size on the mechanical properties and neutron shielding performance of composite materials.MethodsFirstly, ethylene propylene diene monomer (EPDM) rubber with good performance such as high temperature resistance, weather resistance, radiation stability, mechanical properties, and high hydrogen content was used as flexible substrate material, and layered boron bitride (BN) with a high thermal neutron absorption cross-section was taken as 2D functional filler, and the surface of BN was modified by mercapto group through two-step chemical grafting. BN/EPDM flexible neutron protection composite materials were prepared by the process of plasticizing, mixing and hot pressing and vulcanization, and the content of BN was controlled at 20~100 phr (parts per hundred parts of rubber), and azodiisobutyronitrile (AIBN) acted as an initiator to promote the interfacial bonding between mercaptylated boron nitride (BN-SH) and EPDM substrate. Then, the microstructures of the materials such as functional group and microscopic morphology were characterized and analyzed using Fourier transform infrared spectrum (FTIR) and scanning electron microscope (SEM). Subsequently, the tensile properties including tensile strength and elongation at break were characterized by universal testing machine, according to GB/T 528―2009 standard. The surface hardness was measured by Shore A hardness tester, according to GB/T 531.1―2008 standard. Finally, the neutron shielding performance was tested based on cadmium sheet difference method, where americium-beryllium source with moderation and collimation was used as narrow beam measurement geometry, and 3He detector was used to count neutrons.ResultsThe experimental results indicate that the reduction of BN size is conducive to improving the tensile strength and thermal neutron shielding performance of composite materials. When the thickness of the material is 2 mm, its tensile strength can reach up to 8.13 MPa, and the thermal neutron shielding rate can be increased by up to about 5%, which is related to the amount of nano BN.ConclusionsThis study confirms the size effect of two-dimensional functional fillers in neutron shielding composite materials, and can provide the basis for the design and preparation of polymer-based flexible neutron protection composites.